OGG1 Inhibition Triggers Synthetic Lethality and Enhances The Effect of PARP Inhibitor Olaparib in BRCA1-Deficient TNBC Cells - Baquero, Juan Miguel; Marchena-Perea, Erik; Mirabet, Rocío; Torres-Ruiz, Raúl; Blanco-Aparicio, Carmen; Rodríguez-Perales, Sandra; Helleday, Thomas; Benítez-Buelga, Carlos; Benítez, Javier; Osorio, Ana (Frontiers in Oncology, 2022)
Background PARP1 plays a critical role in the base excision repair (BER) pathway, and PARP1 inhibition leads to specific cell death, through a synthetic lethal interaction, in the context of BRCA1/2 deficiency. To date, up to five different PARP inhibitors (PARPi), have been approved, nevertheless, the acquisition of resistance to PARPi is common and there is increasing interest in enhancing responses and expand their use to other tumour types. Methods We hypothesized that other BER members could be additional synthetic lethal partners with mutated BRCA genes. To test this, we decided to evaluate the glycosylase OGG1 as a potential candidate, by treating BRCA1 proficient and deficient breast cancer cells with PARPi olaparib and the OGG1 inhibitor TH5478. Results Knocking out BRCA1 in triple-negative breast cancer cell lines causes hypersensitivity to the OGG1 inhibitor TH5487. Besides, TH5487 enhances the sensitivity to the PARP inhibitor olaparib, especially in the context of BRCA1 deficiency, reflecting an additive interaction. Discussion These results provide the first evidence that OGG1 inhibition is a promising new synthetic lethality strategy in BRCA1-deficient cells, and could lead to a new framework for the treatment of hereditary breast and ovarian cancer.